Teleportation-based quantum computation, extended Temperley–Lieb diagrammatical approach and Yang–Baxter equation - Zhang, Yong; Zhang, Kun; Pang, Jinglong (Quantum information processing, 2016)
This paper focuses on the study of topological features in teleportation-based quantum computation and aims at presenting a detailed review on teleportation-based quantum computation (Gottesman and Chuang in Nature 402: 390, 1999 ). In the extended Temperley–Lieb diagrammatical approach, we clearly show that such topological features bring about the fault-tolerant construction of both universal quantum gates and four-partite entangled states more intuitive and simpler. Furthermore, we describe the Yang–Baxter gate by its extended Temperley–Lieb configuration and then study teleportation-based quantum circuit models using the Yang–Baxter gate. Moreover, we discuss the relationship between the extended Temperley–Lieb diagrammatical approach and the Yang–Baxter gate approach. With these research results, we propose a worthwhile subject, the extended Temperley–Lieb diagrammatical approach, for physicists in quantum information and quantum computation.